Implications of cigarette smoking on early‐onset androgenetic alopecia: A cross‐sectional Study. (5th October 2020) - Salem, Ahmed S.; Ibrahim, Hany S.; Abdelaziz, Heba H.; Elsaie, Mohamed L.
Abstract : Background: Androgenetic alopecia (AGA) is a condition affecting both males and females. Aims We aimed to assess the demographic and clinical features of early‐onset AGA among smokers and nonsmokers and to evaluate whether prevalence of AGA was affected by smoking. Paatients/Methods: One thousand (1000) healthy males aged between 20 and 35 years not complaining of any local scalp condition and free of any mental illness were recruited for this study and divided into two groups of 500 each based on their smoking attitudes. Androgenetic alopecia was classified according to the Hamilton baldness scale, and trichoscopy was used to confirm the diagnosis of AGA. A designed questionnaire to determine basic physical and smoking habits completed and results was interpreted and analyzed. Results: The majority of smokers (425) had a form of AGA, while only (200) nonsmokers had a degree of AGA ( P  < .01). Of the smokers group, 235 (47%) had grade III AGA and 120 subjects (24%) had grade IV AGA. In the nonsmokers group, 100 subjects (20%) had grade II AGA and 50 subjects (10%) had either grade III or IV AGA. Conclusion: The prevalence of AGA among smokers was statistically higher than among nonsmokers, while severity of AGA was not associated with the intensity of smoking. Nicotine and its derivative cotinine might be responsible for accelerating AGA progress pending further validation.